Nonalternant Extension of Multiple Resonance Emitter via Palladium-Catalyzed [5 + 2]-Annulation - Zhuang, Weiwen; Chong, Waiming; Liu, Junzhi (Organic Materials, 2025)
Despite the proliferation of multiple resonance (MR) emitters with rigid 1,4-azaborine-based skeletons, the straightforward and efficient incorporation of nonhexagonal rings, especially for heptagons remains elusive. Here, a green–yellow emitter consisting of two azepines was designed and synthesized via a palladium-catalyzed one-pot twofold [5 + 2]-annulation reaction with high selectivity and efficiency. The tetrabenzene-fused benzo[1,2-b:5,4-b']bis(azepine) (TBBBA) core induced a highly twisted and dynamically helical rim for the novel MR-skeleton, which reduced π–π stacking in the solid state. Moreover, the nonalternant topology facilitated the delocalization of frontier molecular orbitals (FMO) within the twisted geometry, thus achieving red-shifted narrow emission. Our work provides a new synthetic strategy toward nonalternant extension of MR-emitters and gives insights into the electronic effects of multiple azepination on FMO distribution.
Keywords: nonalternant extension; multiple resonance; annulation; azepines.